2017
DOI: 10.1039/c7ra10063a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydrolysis and ethanol production from rice straw by pretreatment with organic acids and effluent of biogas plant

Abstract: Effects of biogas effluent and its organic ingredients, i.e., acetic, butyric, lactic, and propionic acid, for the pretreatment of rice straw on enzymatic hydrolysis and ethanol production was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…cellulolytic consortium [22] or untreated wheat straw [20]. Higher xylose and glucose in FR groups is a result of efficient hydrolysis of hemicelluloses and cellulose, which highlights the potential of using rumen inoculum of Barki sheep in the bioconversion of lignocellulosic biomass compared to rumen inoculum of camel [16].…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…cellulolytic consortium [22] or untreated wheat straw [20]. Higher xylose and glucose in FR groups is a result of efficient hydrolysis of hemicelluloses and cellulose, which highlights the potential of using rumen inoculum of Barki sheep in the bioconversion of lignocellulosic biomass compared to rumen inoculum of camel [16].…”
Section: Plos Onementioning
confidence: 98%
“…Lignocellulosic biomass from plant residues is a suitable alternative to food crops in the production of second-generation bioethanol [18][19][20]. A huge amount of straw (dried stalks of grain plants) is generated globally every year; therefore straw is considered a renewable source of energy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Kadam et al [2] suggested that each ton of grain harvested leaves 1.35 tonnes of rice straw in the field. Hence, annual global production of rice straw is of the order of 650–975 million tonnes [3]. This rice straw is usually either burnt in the open atmosphere or dumped into landfills.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Beside solubilization of hemicellulose, using these chemicals can remove lignin and reduce lignin-cellulose-xylan interactions, leading to higher cellulose digestibility. [26][27][28] Despite increasing sugar yield in subsequent hydrolysis processes, adding chemicals for the pretreatment are connected to some drawbacks including increasing costs, equipment corrosion, high energy consumption, pH neutralization requirement, and formation of inhibitory by-products. 1,29,30 Therefore, using a waste stream, that consists of effective elements, such as acids and bases, instead for the pretreatment would be more benecial.…”
Section: Introductionmentioning
confidence: 99%